Uses of Sand Dunes as Building Materials - J. Al-Shakeri, Ahmed; K. Jasim, Hasan; H. Abdullah, Hamed; K. Kadhum, Ali; H. Thwani, Hind (Iraqi Journal of Science, 2021)
During the past forty years, and due to the global climate changes, Iraq had and still suffering from the spreading and expansion of large dune fields in which many new generations have been accumulated, and older ones have expanded leading to the desertification of huge agricultural and urban areas and causing vast environmental problems that have a drastic effect on the life style of the population. To tackle such a problem, many methods have been suggested and even more are applied to fix the dunes or at least to limit their spreading so that to lessen the environmental impact. Such efforts were tried in many dune areas in Iraq, but it was in vain due to the classical nature of remedy that deals only with temporary and limited results, and in many cases worsening the problem. This is evidenced from the increased nature of dune fields in both area and problems.In this study four major dune fields expanding along four governorates in middle and southern Iraq were studied minerallogically, texturally, and chemically to attest their suitability as fine aggregate for concrete mixtures. These sands are composed of major quartz, feldspars, and calcite minerals, and are devoid of fines (clays), organic matters, and salts. Explicit dune sands of the studied area are not suitable as fine aggregate due to their poor grading, trial on mixing these sands with well-graded river sand (Dibhdiba Formation Sand) in different proportions show that the 35% is optimal for normal load works. Al-Muthana dune sands show the highest evaluations. Missan dune sands were further tested for producing pavement interlock bricks, the results confirmed their aptness for exploitation both economically and environmentally.